A Whole Leaf Comparative Study of Stomatal Conductance Models - Sakurai, Gen; Miklavcic, Stanley J. (Frontiers in Plant Science, 2022)
We employ a detailed whole leaf hydraulic model to study the local operation of three stomatal conductance models distributed on the scale of a whole leaf. We quantify the behavior of these models by examining the leaf-area distributions of photosynthesis, transpiration, stomatal conductance and guard cell turgor pressure. We gauge the models' local responses to changes in environmental conditions of carbon dioxide concentration, relative humidity and light irradiance. We found that a stomatal conductance model that includes mechanical processes dependent on local variables predicts a spatial variation of physiological activity across the leaf: the leaf functions of photosynthesis and transpiration are not uniformly operative even when external conditions are uniform. The gradient pattern of hydraulic pressure which is needed to produce transpiration from the whole leaf is derived from the gradient patterns of turgor pressures of guard cells and epidermal cells, and consequently leads to nonuniform spatial distribution patterns of transpiration and photosynthesis via the mechanical stomatal model. Our simulation experiments, comparing the predictions of two versions of a mechanical stomatal conductance model, suggest that leaves exhibit a more complex spatial distribution pattern of both photosynthesis and transpiration rate, and more complex dependencies on environmental conditions, when a non-linear relationship between the stomatal aperture and guard cell and epidermal cell turgor pressures is implemented. Our model studies offer a deeper understanding of the mechanism of stomatal conductance, and point to possible future experimental measurements seeking to quantify the spatial distributions of several physiological activities taking place over a whole leaf.